NORMALISASI RIBA FADHL PADA PENGGUNA JASA PENUKARAN UANG MUSIMAN DI WASTUKENCANA: TINJAUAN SOSIOLOGI EKONOMI - Tsaqifulfawwaz Tsaqifulfawwaz; Fadiyah Syifa Nurrochim; Nashita Aisha Luky; Dinda Aisyah Febrianty; Binyamin Raftli Affendi (AGHNIYA : Jurnal Ekonomi Islam, 2026)
The normalization of prohibited financial practices in Muslim communities is a persistent challenge in Islamic economics. Seasonal informal money exchange during Eid al-Fitr exemplifies how Riba al-Fadhl unequal exchange of homogeneous currencies  becomes embedded in collective tradition, exploiting low-income groups and distorting market fairness. This study analyzes the normalization dynamics of Riba Fadhl in seasonal informal money exchange services in Wastukencana, Bandung, through an economic sociology perspective. The research employs a qualitative-investigative approach, adapting norm elicitation via a 2×2 observation matrix manipulating time urgency and social proximity. Results indicate moral compliance is flexible and reconstructed under situational pressures, driven by cognitive dissonance. Norm violations predominantly occur during high-urgency periods, particularly before Eid al-Fitr, and in transactions involving familiar providers. Individuals utilize neutralization techniques employing euphemisms like "service fee" to reduce moral tension. Ultimately, ethical norms are dynamically reinterpreted to meet pragmatic needs, proving that ethical preferences adapt to contextual pressures.